Effect of cooling media on hardness and microstructural changes in S45C carbon steel during heat treatment process - Bambang Hari Priyambodo; Reni Laili; Rizqi Ilmal Yaqin; Suhartoyo Suhartoyo (Jurnal POLIMESIN, 2023)
S45C Carbon steel is commonly used in the manufacturing of structural or machine components due to its numerous advantages. However, to fulfill its intended purpose, the mechanical properties of this material require improvement. One approach to achieve this is through heat treatment using different cooling fluids. Therefore, this study aimed to examine the effect of varying cooling fluids on heat treatment of S45C carbon steel, specifically its hardness and microstructure changes. The experimental method employed involves heating the specimens in a furnace at 850oC for 30 minutes, followed by cooling using different fluids, namely water, ice water, and oil. The results showed that faster cooling led to an increase in hardness. In particular, the specimens cooled using water, ice, and oil yielded hardness values of 697 HV, 481 HV, and 248 HV, respectively. The highest hardness value of 697 HV was achieved using ice water, indicating an increase of around 281%. The phase changes observed on the surface of the specimen showed the dominance of martensite.